PROJECTIONS IN ENGLISH NOVELS AND THE QUEST FOR IDENTITIES IN MUSLIM AND ARABIC GENERATIONS - Lecturer, Fouad Abbas Ali (European Journal of Humanities and Educational Advancements, 2023)
Following the September 11th attacks in the United States, the western media portrayed an outlandish image of Arab Muslim character. columnists who continue to portray them in a negative light. As a result, weapons like speculation, orientalism, hybridity, and partiality are employed by the enemy. Westerners are attempting to distort the image of Arab Muslims. They portray them as oppressors based on fear, fundamentalists, radicals, and so on. jihadist. As a result, they continue to portray them in the same way that postpioneer writers depicted them in the past. see the Arab and Muslim worlds from their own unique point of view. Surprisingly, Arab writers strive to portray them as accurately as possible. As you can see, the events that occurred after the strike had a significant impact on the system. They strive to send a timely message in this direction. The Arabs and Muslims in the west are abused and influenced by the ambush as much as the westerners themselves. They also make an effort to highlight what Arabs and Muslims are thinking about in terms of congruity and modern living They could wish to be something along these lines. facilitated with created people in Western nations, so that they may engage in the constant life of the West. Furthermore, Arab authors Specify that westerners make a reasonable effort to prevent Arabs from entering their territory and from driving their own vehicles. nations without reservation. As a result, the West is attempting to unite its strength against the Arabs and Muslims via a variety of perverted means. pictures. In the same manner, I’ll take a careful look at how the Arab Muslim persona is portrayed in both Western and Asian media. The perspective of the Arabs. As a result, I chose four novels, two of which were written by two American authors and two of which were written by two Arab authors. After the incident, authors should provide a broad, specific portrait of the Arab Muslims’ character. As a result, the picture following the assault will be more realistic. It had been warped, deformed, and entangled in any case, with one piece of the investigation reprimanding the other. During and after the ambush, on the other hand. I shall disregard how different scholars approach the relevant books. I’ll manage them differently since I’ll be looking at them from various angles. As a result, the project will look at Orientalism, fanaticism, and other related topics. In these mentioned texts, there are hypotheses and hybridity to investigate the image of Arab Muslim character after September 11th. In America, there is a strike. Muslim Arab Identity, Muslim Status, and the Search for Muslim Identities between the writers of the West and the Arab world The examination is in progress.